Characteristics of denitrifying granular sludge grown on nitrite medium in an upflow sludge blanket (USB) reactor - Jin, Xibiao (Water science and technology : a journal of the International Association on Water Pollution Research, 2012)
While inoculating pre-acclimatized floccular sludge, nitrite-denitrifying granular sludge was obtained after approximately 40 days of cultivation in a 10 L upflow sludge blanket (USB) reactor. The nitrite removal efficiency was approximately 95% when the nitrite concentration was 50 mg L(-1)at an influent flow rate of 20 L h(-1). The nitrite granular sludge had several notable features including good settleability (110 m h(-1)), high ash content (79%), and high density (1.248 g cm(-3)). The mixed liquor suspended solids (MLSS) of the sludge bed remained at 130.04 g L(-1), at a hydraulic upflow velocity of 2 m h(-1). These interesting characteristics were attributed to a high effluent pH (9.7) caused by the release of alkalinity during the nitrite denitrification process. The surfaces of the granules were dominated by cocci bacteria with a diameter of approximately 3 μm, which could be classiﬁed as Nitrosomonas-like species based on our analysis of 16 S rDNA sequences